Strategic Assessment of AIMS Students’ Learning Opportunities and Challenges During the New Normal - Giner, Rhogin V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study examines the learning opportunities and challenges faced by students at the Asian Institute of Maritime Studies (AIMS) in response to the sudden shift to online learning during the Covid-19 pandemic. AIMS, like many educational institutions in the Philippines, adapted to the new normal setting by implementing online learning with all its facets. While this setup opened up new opportunities for students, it also presented various challenges. The research involved 337 AIMS students from the 2021-2022 academic year, using a descriptive-comparative design to assess differences in opportunities gained and challenges experienced. The participants were selected through a combination of purposive and random sampling. Data was collected using a standardized instrument consisting of three parts: profiling respondents, determining opportunities gained using the "Synchronous Online Teaching Observation Checklist" from the City University of New York (2020), and assessing challenges through the self-report online learning challenge questionnaire by Barrot et al. (2021), modified for the study. Statistical tools such as frequency, percentage, weighted mean, T-test, and ANOVA were utilized for data analysis. Results indicated that students perceived opportunities in Assessment and Feedback, Student Engagement, Learning Environment, Time Management, and Instructional Design. On the other hand, they expressed neutrality towards challenges related to Technological Sufficiency, Student Isolation, Technological Complexity, Self-Regulation, and Learning Environment. Further analysis revealed significant differences in learning opportunities based on gender and program. Recommendations include providing platform usage training, offering specialized learning activities based on courses and programs, and ensuring gender-sensitive learning opportunities.